2003
DOI: 10.1007/s10334-003-0001-0
|View full text |Cite
|
Sign up to set email alerts
|

Subchondral bone and cartilage thickness from MRI: effects of chemical-shift artifact

Abstract: Magnetic resonance imaging (MRI) is the modality of choice for visualizing and quantifying articular cartilage thickness. However, difficulties persist in MRI of subchondral bone using spoiled gradient-echo (SPGR) and other gradient-echo sequences, primarily due to the effects of chemical-shift artifact. Fat suppression techniques are often used to reduce these artifacts, but they prevent measurement of bone thickness. In this report, we assess the magnitude of chemical-shift effects (phase-cancellation and mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 46 publications
2
28
2
Order By: Relevance
“…Special consideration must be given to the SB thickness comparisons, however. As we showed previously (16), the apparent SB thickness is affected by both phase‐cancellation and misregistration effects caused by chemical shift. Phase‐cancellation effects can be minimized by using an in‐phase TE (such as 13.5 msec), which we used in our imaging protocol.…”
Section: Methodssupporting
confidence: 72%
See 2 more Smart Citations
“…Special consideration must be given to the SB thickness comparisons, however. As we showed previously (16), the apparent SB thickness is affected by both phase‐cancellation and misregistration effects caused by chemical shift. Phase‐cancellation effects can be minimized by using an in‐phase TE (such as 13.5 msec), which we used in our imaging protocol.…”
Section: Methodssupporting
confidence: 72%
“…However, one way to eliminate misregistration effects is to acquire separate water and fat suppressed images, followed by addition of the separate images (creating a single water and fat image). In our prior report (16), we found that a simple trigonometric correction factor applied to the thickness vector's readout direction gave a good approximation of the subchondral bone thickness from the combined water and fat images. Thus, we compared SB thickness from Faxitron‐based measurements to thickness from MRI‐based measurements with and without this correction.…”
Section: Methodsmentioning
confidence: 83%
See 1 more Smart Citation
“…Differentiation of the deep layers of articular cartilage and subchondral bone using routine MRI is difficult [18][19][20]. The transition between cartilage and bone will appear to vary depending on factors such as TE and the orientation of the cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…Cortical bone surface irregularities to previously described and well-known chemical shift and susceptibility artefacts occurring at the bordering regions between cortical bone and cartilage, fluid or soft-tissue structures of the TMJ [10][11][12][15][16][17][18][19]. The resulting overor underestimation, however, may lead to misinterpretation of the cortical bone surface and structure.…”
Section: Cortical Bone Thinningmentioning
confidence: 99%